Peran Pengajian Gus Iqdam dalam Internalisasi Nilai-Nilai Islam Moderat - Muhammad Rois; Bachrurrosyady Amrulloh, Moch. (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the process of internalizing the values of moderate Islam through the religious lectures of Gus Iqdam at Majelis Ta’lim Sabilu Taubah, Blitar, within the context of Indonesia’s plural society that remains vulnerable to intolerance and radicalism. The research employs a qualitative method with an ethnographic design, specifically utilizing participant observation, in-depth interviews with Gus Iqdam, administrators, and congregants, as well as documentation studies, including social media content analysis. The collected data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the internalization of religious moderation is carried out through five main methods: humorous and communicative preaching, exemplary conduct (uswah hasanah), the utilization of social media, an inclusive approach toward marginalized groups, and dialogical-participatory methods. Its implementation is reflected in the cultivation of the values of justice (al-‘adl), balance (tawazun), tolerance (tasamuh), inclusivity, and compassion (rahmah) alongside non-violence. These values are not only conveyed verbally but are also practiced in daily interactions and social activities of the assembly, resulting in positive behavioral transformation and strengthened social cohesion within the community.